Pharmacokinetics of butorphanol following intravenous and intramuscular administration in donkeys: A preliminary study - Ebner, Lisa; O, Odette; Simon, Bradley; Lizarraga, Ignacio; Smith, Joe; Cox, Sherry (Frontiers in Veterinary Science, 2022)
The pharmacokinetics of butorphanol after intravenous (IVB) and intramuscular (IMB) administration in donkeys were determined in this preliminary study. Healthy male gelded donkeys (n = 5), aged 6–12 years old, were administered 0.1 mg/kg butorphanol IV or IM in a randomized, crossover design. Blood samples were obtained at predetermined intervals for 24 h (IVB) and 48 h (IMB) after administration. Plasma butorphanol concentrations were determined by high performance liquid chromatography and pharmacokinetic parameters were calculated. Following IVB administration, mean (± SE) apparent volume of distribution, elimination half-life, total body clearance, and area under the plasma concentration time curve from time 0 to infinity (AUC0−∞) were 322 ± 50 mL/kg, 0.83 ± 0.318 h, 400 ± 114 mL/h/kg, 370 ± 131 h·ng/mL, respectively. After IMB administration, a maximum plasma drug concentration of 369 ± 190 ng/mL was reached at 0.48 ± 0.09 h. The IMB AUC0−∞ was 410 ± 60 h·ng/mL. Bioavailability of IMB was 133 ± 45%. The pharmacokinetics of butorphanol in healthy donkeys was characterized by faster elimination half-life compared to values from the equine literature.